Soman-induced toxicity, cholinesterase inhibition and neuropathology in adult male Göttingen minipigs. (2021) - Lumley, Lucille; Du, Fu; Marrero-Rosado, Brenda; Stone, Michael; Keith, Zora-Maya; Schultz, Caroline; Whitten, Kimberly; Walker, Katie; Acon-Chen, Cindy; Wright, Linnzi; Shih, Tsung-Ming
Graphical abstract: Highlights: The median lethal dose of soman (GD) was estimated in adult male Göttingen minipigs. GD exposure induces cholinesterase inhibition and behavioral seizure in minipigs. GD induces neurodegeneration in visual cortex and lateral geniculate nucleus. Prolonged seizure is associated with widespread microglial activation and cell death. The minipig may be a useful alternative large animal model to the non-human primate. Abstract: Animal models are essential for evaluating the toxicity of chemical warfare nerve agents (CWNAs) to extrapolate to human risk and are necessary to evaluate the efficacy of medical countermeasures. The Göttingen minipig is increasingly used for toxicological studies because it has anatomical and physiological characteristics that are similar to those of humans. Our objective was to determine whether the minipig would be a useful large animal model to evaluate the toxic effects of soman (GD). We determined the intramuscular (IM) median lethal dose (LD50 ) of GD in adult male Göttingen minipigs using an up-and-down dosing method. In addition to lethality estimates, we characterized the observable signs of toxicity, blood and tissue cholinesterase (ChE) activity and brain pathology following GD exposure. The 24 h LD50 of GD was estimated to be 4.7 μg/kg, with 95 % confidence limits of 3.6 and 6.3 μg/kg. As anticipated, GD inhibited ChE activity in blood and several tissues. Neurohistopathological analysis showed neurodegeneration and neuroinflammation in survivors exposed to 4.7 μg/kg of GD, including in the primary visual cortex and various thalamic nuclei. These findings suggest that the minipig will be a useful large animal model for assessing drugs to mitigate neuropathological effects of exposure to CWNAs.